Martha Jefferson Randolph, Daughter of Monticello : Her Life and Times - Kierner, Cynthia A., 1958- (Book collections on Project MUSE., 2012)
As the oldest and favorite daughter of Thomas Jefferson, Martha "Patsy" Jefferson Randolph (1772-1836) was extremely well educated, traveled in the circles of presidents and aristocrats, and was known on two continents for her particular grace and sincerity. Yet, as mistress of a large household, she was not spared the tedium, frustration, and great sorrow that most women of her time faced. Though Patsy's name is familiar because of her famous father, Kierner is the first historian to place Patsy at the center of her own story, taking readers into the largely ignored private spaces of the foun.